Assessment of Patients Knowledge towards Angina Pectoris in Kirkuk City - Younis Khider Baez (مجلة الموصل للتمريض, 2015)
Background and aim: Angina pectoris is a clinical syndrome usually characterized by episodes or paroxysms of pain or pressure in the anterior chest. The cause is insufficient coronary blood flow, resulting in a decreased oxygen supply when there is increased myocardial demand for oxygen in response to physical exertion or emotional stress. The aim of the study is to assess patient‘s knowledge toward angina pectoris in Kirkuk city as well as to find out the relation ship between patients knowledge and some Socio- demographic characteristic such as age, gender and level of education Materials and method: A descriptive study of a quantitative design were carried out at Kirkuk general hospital and Azady teaching hospital in Kirkuk city for angina patients from 1st of July, 2012, up to the 16th of April, 2013. A non probability (purposive) sample of (100) definitely diagnosed with angina pectoris. Selected from patients who were attended to Kirkuk general hospital and Azady teaching hospital. Developed questionnaire was constructed for the purpose of the study which consisted of three parts: the demographic data of the respondent, medical data and angina patients knowledge. The data were collected through the use of interview. They were analyzed through the application of descriptive statistical analysis and inferential statistical data analysis. Results: the findings of the study indicated that )(55%) of the samples were in age group (≥60)years, (53%) of them were female, (60%) of the sample were illiterate, (30%) of them were jobless, (68%) of the sample were married, (72%) of the sample had barely sufficient monthly income. Regarding the medical data, the result shows that (81%) of the samples has ( ≤ 5) years duration of the diseases, (70%) of them had no family history of angina, (56%) of them has no working hours, (62%) of the sample had no history of smoking and (40%) of them were over weight. Conclusions: The study concluded that most of the samples have inadequate knowledge about the etiology of angina, most of the samples have adequate knowledge about the risk factors of angina, most of the samples have adequate knowledge about the Clinical manifestation of angina, most of the them have adequate knowledge about the medical treatment of angina and most of them had inadequate knowledge about the invasive treatment of angina. Recommendations: The study recommended that the necessity of educational programs should be designed to increase people knowledge about etiology, signs and symptom and treatment of angina pectoris and Providing scientific booklet, publication and journal about angina. Keywords: Assessment, Knowledge, Angina pectoris, Atherosclerosis, Coronary artery bypass graft, ischemia.